Evaluation of thoracic paravertebral block for pain relief in rib fractures - Tarun Yadav; Gunjan Bansal; Mayuri Golhar; Anju Ghai (National Scientific Medical Center, 2023)
Introduction: Fracture of ribs causes severe pain which in turn activates the cascade of respiratory compromise. Pain management with regional blocks is considered one of the promising techniques. Thoracic paravertebral block (TPVB) is a proven technique considered at par with epidural analgesia. But its blind landmark-based technique has a potential risk of pneumothorax. Ultrasound gives advantage of real time visualization which decreases complications and enhance its success rate. So, we conducted this study to gauge the efficacy and utility of ultrasound guided thoracic paravertebral block. Material and methods: Twenty patients were administered TPVB under ultrasound guidance with 15 milliliters of 0.25 % inj bupivacaine and 2 mg per kg fentanyl who had multiple rib fractures of unilateral hemithorax. For prolonged pain relief a catheter was left in place to administer recurring boluses. The parameters noted were superior costotransverse ligament (SCTL), skin to SCTL distance, skin to pleura distance, VAS at rest & at cough, respiratory rate arterial blood gas parameters at various time intervals. Results: Thoracic paravertebral space was easily identified in each patient with ultrasound. We discovered significant pain relief in terms of VAS score at rest & at cough at different time intervals. Respiratory rate and arterial blood gas parameters improved with the use of ultrasound guided thoracic paravertebral block. Conclusion: Sonographic out of plane sagittal thoracic paravertebral block is a successful technique in rib fracture patients to provide effective pain relief and also ameliorates respiratory rate and oxygenation.